Dayah ANALISIS SEMANTIK PADA KATA AR-RIJAL DALAM QS. SURAH AN-NISA' AYAT 34 - 36 - Mashlahatul Hidayah, Elyfia Qurrotu A'yunina (Institut Agama Islam Pemalang (INSIP) Jawa Tengah, 2025)
Al-Qur'an revealed by Allah SWT aims as a guide for mankind to lead a good life in accordance with the Shari'a. Each of every human being, both male and female, has the obligation to become caliph fil ardi. It has been repeatedly mentioned in the Qur'an that a human being who has the power of reason, responsibility, supports the family, etc. is called lafadz Ar-Rijal. This research was conducted with the aim of knowing more deeply the meaning contained in its entirety in lafadz Ar-Rijal in QS. An-Nisa' verses 34-36 and so that there are no mistakes in interpreting the meaning contained in the lafadz. This type of research is descriptive with library data collection techniques that take primary data from the Al-Qur'an and books, documents or other sources as supporting literature related to the subject matter. Then it is processed and analyzed as well as making conclusions from the collected theories. The author analyzes using various reference sources to reveal the meaning in lafadz ar-rijal.